OPTIMASI NANOSTRUCTURED LIPID CARRIERS (NLC) TERMANOSILASI ACEMANNAN UNTUK PENGHANTARAN RIFAMPISIN MENGGUNAKAN DESAIN BOX-BEHNKEN - Hasna
Tuberculosis (TB) is a respiratory infectious disease caused by Mycobacterium tuberculosis (Mtb) that infects human in active or latent forms. In the latent phase, Mtb is alive as dormant bacillus hiding inside macrophages. This study aims to optimize delivery of antituberculosis drug encapsulated within acemannan-chitosan conjugate-surface modified of nanostructured lipid carriers (NLC) (nanocomposite) using equation models generated by Box-Behnken design to mimic the entry pathway of Mtb. The nanocomposites were prepared by emulsification-solvent evaporation technique followed by ionotropic gelation method by adding STPP. Box-Behnken design was perfomed to optimize various factors in the formula including total lipid, surfactant, and chitosan-acemannan conjugate concentrations to produce optimum particle size, efficiency encapsulation, and drug loading of rifampicin. From the equation model generated by Box-Behnken design, the optimum formula which is 1% rifampicin, 0,75% total lipid (2:1 for cetyl alcohol:oleic acid), 5% polisorbate 80, 0,75% conjugate, and 0,12% STPP, showed particle size of 509.20±11.43 nm, polydispersity index of 0.35±0.03, encapsulation efficiency of 93.76±1.76%, and drug loading of 37.50±0.70% with the errors of the predicted values of 0.47%, 0.34%, and 0.02%, respectively. Narrow deviation from the predicted values indicates a reliable equation model. The optimum formula of nanocomposite had zeta potential value of +2.77 mV and a similar release of rifampicin from nanocomposite at pH 5.2 and pH 7.4. This nanocomposite formula can be further developed to be an intracellular antituberculosis drug.